An investigation into some common errors in using auxiliary verbs made by first - year students at the Faculty of Information Technology - Thai Nguyen University - Nguyễn, Thị Phương Hoa (ĐHNN, 2017)
Auxiliary verbs in English. Types and functions of auxiliary verbs. Sources of errors in using auxiliary verbs. English learners' common auxiliary verbs. Implications for teaching auxiliary verbs. What teachers should take into consideration? Suggested techniques for corrective feedback and for practice?